Stasis and stability : exile, the polis, and political thought, c. 404-146 bc - Gray, Benjamin D. (Oxford classical monographs, 2015)
This study uses exile and exiles as a lens for investigating the later Classical and Hellenistic polis and the political ideas which shaped it. It discusses the rich evidence for varied forms of expulsion and reintegration of citizens of poleis across the Mediterranean, analysing the full range of relevant civic institutions, practices and debates. It also investigates civic activity and ideology outside the polis, addressing the complex and diverse political organisation, agitation and ideas of exiles themselves